The effect of core self-evaluations on career adaptability: The mediating role of protean career attitudes and the moderating role of meritocratic beliefs - Bin Du; Xuan Yu; Nan Luo; Xuhong Liu (Frontiers in Psychology, 2022)
Based on the career construction model of adaptation, this study explores the impact of core self-evaluations on career adaptability, with the mediating role of protean career attitudes and moderating role of meritocratic beliefs. The results of the questionnaire survey on 1000 Chinese college students show that: (1) core self-evaluations positively predicted college students’ career adaptability; (2) protean career attitudes mediated the relationship between core self-evaluations and career adaptability; (3) meritocratic beliefs not only moderated the effect protean career attitudes have on career adaptability but also moderated the indirect influence of core self-evaluations on career adaptability through protean career attitudes. These results extend the existing antecedent studies on career adaptability and demonstrate the importance of combining self-mobility beliefs (protean career attitudes) with social mobility beliefs (meritocratic beliefs) in the process of core self-evaluations affecting career adaptability. In conclusion, we hope to further develop the theory of career construction and provide more suggestions for college consultants and students.